Work Function Characterization of Potassium-Intercalated, Boron Nitride Doped Graphitic Petals - McCarthy, Patrick T.; Paul, Rajib; Zemlyanov, Dmitry; Reifenberger, Ronald G.; Fisher, Timothy S. (Frontiers in Mechanical Engineering, 2017)
This paper reports on characterization techniques for electron emission from potassium-intercalated boron nitride modified graphitic petals. Carbon-based materials offer potentially good performance in electron emission applications owing to high thermal stability and a wide range of nanostructures that increase emission current via field enhancement. Furthermore, potassium adsorption and intercalation of carbon-based nanoscale emitters decreases work functions from approximately 4.6 eV to as low as 2.0 eV. In this study, boron nitride modifications of graphitic petals were performed. Hexagonal boron nitride is a planar structure akin to graphene and has demonstrated useful chemical and electrical properties when embedded in graphitic layers. Photoemission induced by simulated solar excitation was employed to characterize the emitter electron energy distributions, and changes in the electron emission characteristics with respect to temperature identified annealing temperature limits. After several heating cycles, a single stable emission peak with work function of 2.8 eV was present for the intercalated graphitic petal sample up to 1000 K. Up to 600 K, the potassium-intercalated boron nitride modified sample exhibited improved retention of potassium in the form of multiple emission peaks (1.8 eV, 2.5 eV, and 3.3 eV) resulting in a large net electron emission relative to the unmodified graphitic sample. However, upon further heating to 1000 K, the unmodified graphitic petal sample demonstrated better stability and higher emission current than the boron nitride modified sample. Both samples deintercalated above 1000 K.